Anthropometry and athletic performance with Zybek sports in elite American taekwondo athletes - Laurin, L. L. (Scientific Journal of Sport and Performance, 2024)
Introduction: The relationship between anthropometric characteristics and athletic performance in taekwondo athletes is a topic of growing interest in the field of sports science and physical preparation. Objective: To determine the relationship between athletic performance in Zybek Sport tests and anthropometry in elite American taekwondo athletes. Methodology: A quantitative, descriptive, and correlational quasi-experimental cross-sectional study was conducted on a sample of (n = 470) taekwondo athletes. Anthropometric measurements included height, weight, and BMI. Athletic performance was assessed using Zybek Sports Performance Standardized Athletic Testing (SAT®). Results: Negative and statistically significant relationships were identified between the 10 and 20-yard sprints and height (p < .000) and (p < .000), weight (p < .000) and (p < .000), and BMI (p < .016) and (p < .000). The pro Agility test only showed a significant negative relationship with weight (p < .000) and height (p < .000). As for the 40-yard dash, horizontal jump, and vertical jump, which showed positive and significant relationships, it was identified that performance in these tests is influenced by greater height (p < .000), (p < .000), (p < .000), weight (p < .000), (p < .000), (p < .000), and BMI (p < .000), (p < .003) respectively. Except for the vertical jump, which did not show a significant correlation with BMI (p < .542). Conclusion: In conclusion, despite the heterogeneity of the relationships, lower weight, height, and BMI were found to improve performance in the 10 and 20-yard sprints as well as in the pro agility test. In the case of the 40-yard dash, horizontal jump, and vertical jump, greater weight, height, and BMI were related to better performance in these tests, with the exception of the vertical jump, which did not show a significant correlation with BMI.